Matching the Characteristics of Low Wind Speed Turbines with Candidate Wind Regimes. (September 2016) - Mathew, Sathyajith; Lim, Chee Ming; Petra, Mohammed Iskandar; Philip, Geeta Susan; Noorfathin, Maziyyah; Mathew, Manuel S.; Raj, Veena
Abstract: The steady growth of the wind power sector, along with various techno-economic and social constraints, has eventually reduced the availability of sites with high wind energy potential. Hence, the future of wind power developments would shift more towards the sites with low to moderate wind spectra. In this study, the performances of some commercial wind turbines under such low power density wind regimes are modeled and compared. Seven commercial wind turbines by leading manufacturers were considered under this study. The performances of these turbines at three representative sites falling under wind classes 2–3 were modeled. The model combines the Weibull probability density of the wind velocity at the site with the velocity – power response of the turbine. This is then integrated within the productive functional limits of the turbine. The expressions for the energy yield and the capacity factor of the turbine at a given site are presented. A new performance criteria named as Normalized Energy, which is considered to be a better yardstick for comparing the performance of turbines with different Normalized Rated Power, is proposed and used for the analysis. Although the turbines with bigger rotor size showed higher capacity factors at the sites, the Normalized Energy was higher for turbine T2, which comparatively has a lower Normalized Rated Power. It has been identified that, lowering of the cut-in and rated wind speeds along with the design improvements for better velocity power response at lower wind spectra, are the key requirements for the turbines to perform better under low wind velocity regions.